2005
DOI: 10.1007/bf03015767
|View full text |Cite
|
Sign up to set email alerts
|

L’apnée pendant l’induction de l’anesthésie avec du sévoflurane est reliée au mode d’administration

Abstract: P Pu ur rp po os se e: : The incidence and duration of apnea during sevoflurane anesthesia have not been fully characterized. We hypothesized that sevoflurane at slowly increasing concentrations reduces incidence and shortens the duration of apnea compared to administration of a highly concentrated anesthetic mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Previous study has showed that apnea occurred in 16% of patients experienced anesthesia induction with sevoflurane for laryngeal mask insertion [ 34 ]. Pancaro et al have reported that the incidence of apnea during anesthesia induction of sevoflurane ranged from 20% to 68% [ 35 ]. For one thing, the additional propofol was adopted in ‘movement’ patients, which may have resulted in the increased incidence of apnea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has showed that apnea occurred in 16% of patients experienced anesthesia induction with sevoflurane for laryngeal mask insertion [ 34 ]. Pancaro et al have reported that the incidence of apnea during anesthesia induction of sevoflurane ranged from 20% to 68% [ 35 ]. For one thing, the additional propofol was adopted in ‘movement’ patients, which may have resulted in the increased incidence of apnea.…”
Section: Discussionmentioning
confidence: 99%
“…Apnea during anesthesia induction with sevoflurane is correlated with its mode of administration. The faster and higher concentration of sevoflurane is inhaled the higher is the probability the patient will suffer with apnea [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, apnea during the period of anesthesia induction with sevoflurane is associated with its mode of administration. The study by Pancaro et al [ 25 ] showed that apnea occurred in 21%, 20%, 68% of patients induced with sevoflurane at incremental concentrations of 1% (from 1% to 8%), decremental-incremental concentrations of 2% (from 8% to 4% to 8%), and a fixed concentration of 8%, respectively. The higher concentration of sevoflurane is administered, the higher is the probability that the participant will suffer with apnea.…”
Section: Discussionmentioning
confidence: 99%
“…The faster sevoflurane is administered the higher the chance the patient will become apneic. 24 Respiratory irregularities can also contribute to the prolongation of IIAS. The deepening of inhalation anesthesia is obviously hampered by apnea, and this may have contributed to the longer intervals observed in our placebo group before loss of eyelash reflex and PLMA insertion.…”
Section: Discussionmentioning
confidence: 99%